Earnings-related benefits in Ireland: rationale, costs and work incentives - Kakoulidou, Theano; Doolan, Michael; Roantree, Barra (Economic and Social Research Institute, 2022)
Ireland is an outlier among EU countries as it does not have a strong link between previous earnings and the level of payment provided to those who have recently lost their job or are on leave from work for the short- to medium-term for reasons of illness or maternity. This paper provides a historical background for earnings- related benefits in Ireland, outlines the rationale behind linking benefits with previous earnings and examines the potential impact of (re)instating them.
PUBLISHED
Keywords: Inclusive Society